2s-5s=-15s+60

Simple and best practice solution for 2s-5s=-15s+60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2s-5s=-15s+60 equation:


Simplifying
2s + -5s = -15s + 60

Combine like terms: 2s + -5s = -3s
-3s = -15s + 60

Reorder the terms:
-3s = 60 + -15s

Solving
-3s = 60 + -15s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '15s' to each side of the equation.
-3s + 15s = 60 + -15s + 15s

Combine like terms: -3s + 15s = 12s
12s = 60 + -15s + 15s

Combine like terms: -15s + 15s = 0
12s = 60 + 0
12s = 60

Divide each side by '12'.
s = 5

Simplifying
s = 5

See similar equations:

| x-11+x-11+121+121=360 | | x+2y+3z=0 | | -4(x+8)=-32-4x | | 9y+3=5y+10 | | 11x+18=62 | | x+3+x-6=7-4 | | 2/3*7x-9/10 | | -3k-8+7=-21 | | 10y+6=5y+21 | | 1/3xd=1/10 | | x+9-19+x=64-x-1 | | 9=17+3x | | 100y+5=75y+25 | | 8(4-y)+10y=6y | | 19x+(-5)=-26+12x | | M=3m+10 | | 5x+10x+17x+4x=360 | | 16x^3-20x^2+12x-15= | | 4(2+2r)-2(-r+1)=6r+-2r | | M-8=3m+2 | | 21=6(5r-2) | | 3x+3-9=3+7-4 | | 2x+3(x-8)=9-5x | | 8x-25=6x-5 | | 100/15 | | -7x+23=-21-31x | | 36k^3=35 | | 2x+2+6x+1=5x-21 | | -0.7x+2.3=-2.1-3.1x | | -3x=-64+1 | | (5k^2-4k-1/5k^2-12k-7) | | 4y+12=-4(2y+5) |

Equations solver categories